1986
DOI: 10.1111/j.1365-2222.1986.tb00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral antihistamine or nasal steroid in hay fever: a double‐blind double‐dummy comparative study of once daily oral astemizole vs twice daily nasal beclomethasone dipropionate

Abstract: Summary Seventy‐four patients with a well documented history of seasonal allergic rhinitis were randomly allocated to receive either astemizole 10 mg orally per day or beclomethasone 100 μg in each nostril twice daily on a double‐blind double‐dummy basis. The patients were studied in a general practice setting and were seen at entry, during the study and at the end of the study by a single observer, the author. Assessment was by diary card incorporating five 10 cm visual analogue scales related to the four sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Intranasal corticosteroids produced significantly greater relief of total nasal symptoms than did oral antihistamines (−0.42, −0.53 to −0.32). However, there was significant heterogeneity (χ 2 =26.8, P<0.001), with Wood12 showing greater (albeit not significantly) relief of symptoms with oral antihistamines than with intranasal corticosteroids.…”
Section: Resultsmentioning
confidence: 98%
“…Intranasal corticosteroids produced significantly greater relief of total nasal symptoms than did oral antihistamines (−0.42, −0.53 to −0.32). However, there was significant heterogeneity (χ 2 =26.8, P<0.001), with Wood12 showing greater (albeit not significantly) relief of symptoms with oral antihistamines than with intranasal corticosteroids.…”
Section: Resultsmentioning
confidence: 98%
“…According to a meta-analysis of randomized, controlled trials published between 1966 and 1997 comparing oral antihistamines and intranasal corticosteroids, only 2 of 11 studies in which ocular symptoms were evaluated found antihistamines to be superior to intranasal corticosteroids [10]. In both of those studies, the intranasal corticosteroid was beclomethasone [10, 14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…The standardized mean differences for nasal symptoms, both in the individual studies and in the pooled data, consistently favored the INCS with the exception of sneezing in the study by Wood [18]. In Wood's study, the information was presented only in a visual graphic format, making it difficult to assign specific symptom scores.…”
Section: Meta-analysismentioning
confidence: 92%
“…The perception is that inhaled corticosteroids have a slower onset of action, frequently requiring days of therapy before clinical effectiveness is established. A recent review of the literature reveals that in studies designed to look at onset of action, the effect is noted within the first days [18]. If the onset of effect from INCS were several days, it would preclude the use of this class of medication for as-needed therapy.…”
Section: Therapeutic Indexmentioning
confidence: 98%
See 1 more Smart Citation